The effects of submarine alteration and phosphatization on igneous rocks: Implications for Sr-, Nd-, Pb-isotope studies - Geldmacher, Jörg; Hauff, Folkmar; Dürkefälden, Antje; Sano, Takashi; Garbe-Schönberg, Dieter; Portnyagin, Maxim; Hoernle, Kaj (Chemical geology, 2023)
A suite of fresh and variably phosphatized submarine volcanic rock samples from NW Pacific seamounts from the Mid Cretaceous were subject of a detailed trace element and isotopic leaching study to examine the effect of phosphate alteration on the use of Sr-, Nd-, and Pb- radiogenic isotope systems. The study particularly focuses on the behavior of the respective parent/daughter element pairs during phosphatization and leaching in order to evaluate the impact on radiogenic ingrowth correction (“age correction”) for old seafloor samples and their use in geochemical studies. For this purpose, variably intense leaching procedures (no leaching; 2 M HCl at 70 °C for 1 h; 6 M HCl at 130 °C for 3 h) were applied to diverse sample materials (rock powder, rock chips and fresh volcanic glass chips). Phosphatization causes significant modification of isotope ratios and elemental proportions of most trace elements including the rare earth elements. As opposed to common seafloor weathering, Rb/Sr decreases in the lavas with increasing phosphatization, while U/Pb enrichment appears slightly amplified. Mild acid leaching of rock chips, however, generally yields Sr, Nd and Pb isotope ratios largely in accordance with values from fresh glass fractions of the same samples and comparable with the results for similarly leached rock powders. Applying original (non-leached) elemental concentration ratios for the radiogenic age correction of mildly leached sample chips produces mixed results for 87Sr/86Srin but generally agrees with expected 143Nd/144Ndin, 206Pb/204Pbin, 207Pb/204Pbin, and 208Pb/204Pbin values. All residua of strongly leached powders yield significantly more radiogenic 206Pb/204Pbm, 143Nd/144Ndm and higher U/Pb than mildly leached rock chips or powders or even non-leached powder of the respective samples, opposite to what is expected when removing seawater-derived secondary phases by stronger acid leaching. We suggest that this enrichment, after removal of most of the magmatic Pb and Nd, reflects minor refractory components that formed in association with the phosphatization and developed high 206Pb/204Pb ratios by radiogenic ingrowth since the eruption of these lavas in the Mid Cretaceous due to high U/Pb. Utilizing modeled parent/daughter ratios based on magma evolution systematics of associated fresh glass yields no satisfying initial isotopic compositions for the strongly leached samples despite supposed removal of secondary isotopic signals upon leaching. Applying the modeled parent/daughter ratios to age correct mildly leached sample chips and powder otherwise slightly improves the accordance with their respective fresh glass fractions for 208Pb/204Pbin but yields similar results as if using the actual parent/daughter ratios for 143Nd/144Ndin, 86Sr/87Srin, 206Pb/204Pbin, and 207Pb/204Pbin. •Phosphatization of submarine igneous rocks differs from common seafloor alteration.•The usual increase of Rb/Sr is counterbalanced by phosphatization.•The increase of U/Pb is slightly amplified by phosphatization, while Sm/Nd decreases.•Mild (2 M HCl) acid leaching before sample digestion is generally sufficient.•Strong leaching leaves a refractory component with exceptionally high Nd isotope ratios.